(Kadar LDL dan HDL Dalam Darah Model Tikus Periodontitis (Blood Level of LDL and HDL in Periodontitis Rat Model ) - Nugraha Agung Marda; Suci Wulan Agustin; Susilawati Ayu Dewa (Pustaka Kesehatan, 2014)
Backgroud. Increased levels of low density lipoprotein (LDL) and decreased levels of high density lipoprotein (HDL) in the blood is a risk factor for atherosclerosis leading to Coronary Heart Disease (CHD). Risk factor of atherosclerosis are multifactorial such as consuming high lipid diet, excessive eating, sedentary, and inflammatory response. According to the recent study indicated that inflammatory response could affect LDL and HDL blood levels that related to the risk of atherosclerosis lesion formation. Therefore, we suspected that periodontitis could affect LDL and HDL. Purpose. The purpose of this study was to show the effect of periodontitis in LDL and HDL. Methods. This experimental study used the post test only control group design. The object were 8 male wistar rats (Rattus norvegicus) with inclusion criterias were male rats, ±200 gr body weight, 3-4 months age, having a healthy condition, good appetite, and normal behavior. The rats were devided into two groups, i. e. control group and treatment group (periodontitis group) with 4 rats in each group. Periodontitis rat model was created by fitting cervical left low molar tooth with wire ligature and injected with 0,02 ml P. gingivalis ATCC 33277 (dosage 5µg/0,05 ml) in bucal sulcus, three times a week for 4 weeks (28 days), all of the rats were fed with standard diet. On day 29th all groups of rats were sacrificed and intracardial blood were taken 3 cc for examination of LDL and HDL blood levels by electrospectrophotometric method. Data were analyzed by T-test. Result. Result showed that periodontitis rat model had a significantly higher LDL levels compared to control group (P <0,05) and HDL levels were lower than controls, but the difference was not significant (P >0,05). Conclusion and suggestion. Based on this study periodontitis increase LDL blood levels. Further research related with duration of periodontitis are needed because periodontitis is usually a chronic disease and have a long lasting effect . In addition, the role of the severity of periodontitis are required to learn.   Keywords: HDL, LDL, Periodontitis.